2017
DOI: 10.1007/s11747-017-0557-2
|View full text |Cite
|
Sign up to set email alerts
|

Sales force leadership during strategy implementation: a social network perspective

Abstract: Many new marketing strategies falter in the execution phase where managers fail to make frontline employees fully committed to implementing the new initiatives. While formal managers can apply transformational and transactional leadership behaviors to increase salespeople's strategy commitment, peers can also exert a great deal of informal influence on salespeople. Building on recent social network perspectives of leadership, this paper investigates the interplay between the sales manager's leadership styles a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 61 publications
(107 reference statements)
1
19
0
Order By: Relevance
“…First, we take the notion of salesperson heterogeneity as a starting point and apply configurational thinking to demonstrate that a large-scale sales force transformation features equifinal paths to the intended outcome among a heterogeneous sales force. Prior studies have, with a few exceptions, sought to identify universal antecedents that will generally result in intended outcomes when applied across the entire sales force (e.g., Hayati et al 2018;Homburg et al 2010;Hunter and Panagopoulos 2015;Johnson and Sohi 2017). However, as suggested by Ahearne et al (2010) and shown in this study, salespeople differ in their ability to change whereby a universal application of transformation conditions across the salesforce may not be the best approach to achieve complex transformations.…”
Section: Theoretical Implicationsmentioning
confidence: 86%
See 3 more Smart Citations
“…First, we take the notion of salesperson heterogeneity as a starting point and apply configurational thinking to demonstrate that a large-scale sales force transformation features equifinal paths to the intended outcome among a heterogeneous sales force. Prior studies have, with a few exceptions, sought to identify universal antecedents that will generally result in intended outcomes when applied across the entire sales force (e.g., Hayati et al 2018;Homburg et al 2010;Hunter and Panagopoulos 2015;Johnson and Sohi 2017). However, as suggested by Ahearne et al (2010) and shown in this study, salespeople differ in their ability to change whereby a universal application of transformation conditions across the salesforce may not be the best approach to achieve complex transformations.…”
Section: Theoretical Implicationsmentioning
confidence: 86%
“…First, transformations depend on individual salesperson characteristics related to change, such as attitudes, abilities, and behaviors (Ahearne et al 2010;Johnson and Sohi 2017;van der Borgh and Schepers 2018;Wieseke et al 2008). Second, sales management can drive change through its emphasis, leadership styles, information provision, sales tools, organizational resources, or training (Hayati et al 2018;Morgan and Inks 2001;Terho et al 2017;van der Borgh and Schepers 2018;Zablah et al 2012). Third, social influence by experts, peers, leaders, or appointed champions can lead to change (Avlonitis and Panagopoulos 2005;Keränen and Liozu 2020;Wieseke et al 2008Wieseke et al , 2009.…”
Section: Sales Force Transformation Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Social networks are conduits of transmission of information in many areas such as municipalities (Bonsón et al, 2015;Bonsón et al, 2012;Park et al, 2016), hospitals (Gittelman et al, 2015;Glover et al, 2015), media (Fernandez Gomez and Diaz-Campo, 2014), tourism marketing (Ketter, 2016;Kiralova and Pavliceka, 2015;Mariani et al, 2016;Martinez-Valerio, 2012), companies and industries (Hayati et al, 2018;Mills and Plangger, 2015;Song et al, 2018;Yuki, 2015), students and teachers (Asterhan and Bouton, 2017;Kondakci et al, 2018;Van Waes et al, 2018), agriculture (Bao et al, 2018), energy (de Paulo and Porto, 2017), archaeology (Mills, 2017) and even academic articles (Haustein et al, 2015;Ringelhan et al, 2015), among other areas.…”
Section: Institutional Dialogue By Means Of Social Media and Challengmentioning
confidence: 99%